Convergence clubs of economic liberalization in ASEAN, China, and India - Rossazana Ab-Rahim,; Sonia Kumari Selvarajan,; Nor-Ghani Md-Nor,; Dayang Affizah Awang Marikan, (Penerbit Universiti Kebangsaan Malaysia, 2018)
The emergence of China and India as major international forces alongside ASEAN has triggered interest in strengthening the economic ties between these countries; hence, this serves as the motivation for this study to embark upon an analysis on economic liberalization and its link to economic growth. The present study also aims to examine the possibility of convergence clubs to exist between ASEAN, China, and India. The pooled mean group (PMG) estimator approach was employed to assess the dynamic effects of economic liberalization, while Phillips and Sul methodology was used to assess the economic possibility of convergence clubs. The empirical evidence supports the positive nexus between economic liberalization and economic growth of ASEAN, China and India for the 1988 to 2014 period. The results also offered support to the hypothesis that not all countries converge to a single equilibrium state, and the results of Philips and Sul’s method revealed the existence of three convergence clubs. The first club consists of Singapore and Brunei Darussalam, the second club is represented by Thailand, China, and Indonesia, while the third group comprises of the Philippines, India, Vietnam, Lao PDR, and Myanmar. Interestingly, Malaysia was found to be the only outlier among the selected countries under study.